Comportamiento de la función respiratoria en remeros cubanos durante un test remoergométrico de 2000 m - Martinez la Rosa, R. M.; Gonzalez Revuelta, M. E.; Llera Crespo, A. (Revista Cubana de medicina del deporte y la cultura fisica, 2016)
In order to characterize the respiratory function of Cuban rowers during a stress test of 2000 m, 29 athletes of the National Team of Cuba, 21 males (10 open weight MPA and 11 lightweight MPL) and 8 females (4 open weight FPA and 4 lightweight FPL) coupling a Concept2 rowing ergometer to a gas analyzer ERGOCIT AT PLUS. A descriptive and analytic cross -sectional study, determining ergospirometric different variables such as respiratory rate, minute ventilation, the VD / VT ratio and ventilatory equivalent of O2 and CO2 in the rest, at 1000 meters, and the end of the test, was performed. Data were recorded and later analyzed with the statistical package SPSS 17, determining descriptive statistics of all variables during the three mentioned moments, which allowed us to characterize the respiratory function of athletes during the test. Men showed higher values of minute ventilation that women, at the expense of the respiratory rate and higher values of VD / VT ratio especially during the flight of the first 1000 meters, denoting a greater commitment of ventilatory efficiency. Results allowed to make recommendations to the training plan.